The influence of an invasive plant on denitrification in an urban wetland. (8th February 2018) - Roley, Sarah S.; Tank, Jennifer L.; Grace, Michael R.; Cook, Perran L.M.
Abstract: Wetlands are often biogeochemical hotspots, and they can remove excess N via denitrification and assimilatory uptake. Wetlands are also susceptible to plant invasions, but the effect of invasive plants on denitrification in freshwater wetland sediments is not well‐studied. Two distinct mechanisms suggest the potential for invasive plants to alter denitrification. First, invasive plants often produce more biomass than non‐invasive species, thus potentially providing additional carbon (C) for denitrifiers. Second, some invasive wetland plants funnel more oxygen into the root zone than non‐invasive plants, potentially stimulating coupled nitrification–denitrification. Using the push–pull isotope pairing technique, we measured denitrification and coupled nitrification–denitrification in the sediments beneath monoculture plots of Phragmites australis and Typha domingensis, and beneath unvegetated sediments, in an urban wetland in Melbourne, Australia. We also measured pore water nutrient concentrations and calculated the diffusive flux of nutrients from the sediments into the overlying water column. We hypothesised that plots containing P. australis would have the highest denitrification and coupled nitrification–denitrification rates, followed by plots containing T. domingensis, with the lowest rates in the unvegetated plots, as a result of higher C and oxygen availability. Instead, we found that denitrification and coupled nitrification–denitrification rates were highly variable, with no difference among plot type. However, we did find that diffusive flux of ammonium from the sediments into the water column was lower in the vegetated plots than in the unvegetated plots, suggesting that vegetation enhances wetland N retention via plant assimilatory uptake.